Effect of Oven Drying Temperature on The Tanin Content of Bungur (Lagerstroemia speciosa Auct. non (L.) Pers) Leaves - Upa, Nurul Fatmawati Pua; Kolobani, Matias Nataniel; Wardani, Nimas Prita R.K; Kale, Maria Laurenci Fanny Permata; Tunggal, Deif (Manunggal Halim Jaya, 2024)
A study was conducted on the effect of oven drying temperature on tannin content of bungur leaves (Lagerstroemia speciosa Auct. non (L.) Pers). Bungur leaves were picked, dry sorted, washed, wet sorted, and drained then oven dried at 30oC, 60(o)C, 90oC respectively. After drying, the samples were then measured for moisture content and then made into bungur leaf powder. Bungur leaf powder was then extracted by modified maceration using aquadem solvent. The extract obtained was tested qualitatively and quantitatively. Qualitative test results showed the presence of tannins. Quantitative tests using permanganometry, obtained tannin levels at drying temperatures of 30oC, 60oC, and 90oC were 7.27% ± 0.1429, 15.26% ± 1.0610, and 9.92% ± 0.7156, respectively. The highest tannin content was obtained at 60oC drying temperature.